Predictors and prevention of diabetic cardiomyopathy - Chavali V (Dove Medical Press, 2013)
Vishalakshi Chavali, Suresh C Tyagi, Paras K Mishra Department of Physiology and Biophysics, School of Medicine, University of Louisville, Louisville, Kentucky, USA Abstract: Despite our cognizance that diabetes can enhance the chances of heart failure, causes multiorgan failure,and contributes to morbidity and mortality, it is rapidly increasing menace worldwide. Less attention has been paid to alert prediabetics through determining the comprehensive predictors of diabetic cardiomyopathy (DCM) and ameliorating DCM using novel approaches. DCM is recognized as asymptomatic progressing structural and functional remodeling in the heart of diabetics, in the absence of coronary atherosclerosis and hypertension. The three major stages of DCM are: (1) early stage, where cellular and metabolic changes occur without obvious systolic dysfunction; (2) middle stage, which is characterized by increased apoptosis, a slight increase in left ventricular size, and diastolic dysfunction and where ejection fraction (EF) is <50%; and (3) late stage, which is characterized by alteration in microvasculature compliance, an increase in left ventricular size, and a decrease in cardiac performance leading to heart failure. Recent investigations have revealed that DCM is multifactorial in nature and cellular, molecular, and metabolic perturbations predisposed and contributed to DCM. Differential expression of microRNA (miRNA), signaling molecules involved in glucose metabolism, hyperlipidemia, advanced glycogen end products, cardiac extracellular matrix remodeling, and alteration in survival and differentiation of resident cardiac stem cells are manifested in DCM. A sedentary lifestyle and high fat diet causes obesity and this leads to type 2 diabetes and DCM. However, exercise training improves insulin sensitivity, contractility of cardiomyocytes, and cardiac performance in type 2 diabetes. These findings provide new clues to diagnose and mitigate DCM. This review embodies developments in the field of DCM with the aim of elucidating the future perspectives of predictors and prevention of DCM. Keywords: diabetes, obesity, exercise, heart failure, miRNA, oxidative stress